Professors of the Kharkiv Technological Institute: unknown pages of biography - Tverytnykova, Elena; Gutnyk, Maryna; Salata, Halyna (Державний університет інфраструктури та технологій, 2020)
The purpose of the study is to conduct a comprehensive historical and scientific analysis of the life and scientific and organizational activities of professors of the Kharkiv Technological Institute Oleksii Khinkulov and Pavlo Dedusenko, using the study of scientific literature and involved archival materials. On the basis of the involvement of unknown and little-known archival documents, a historical reconstruction of the creative activity of scientists was conducted; in particular, the little-known period of their life in 1940-1946 was studied in detail. A comprehensive analysis of the scientific activities of Oleksii Khinkulov was carried out, his contribution to the formation of the electrical industry was determined. His role in the development of scientific research in the field of radio engineering in Ukraine was emphasized. He headed one of the largest radio engineering club in Ukraine. The social activities of Oleksii Khinkulov were investigated, it was found that for a long time he worked as deputy chairman, and then as chairman of the All-Ukrainian Association of Engineers, which united the teams of research departments of technical institutions of Ukraine. The scientific and organizational activities of Professor Oleksii Khinkulov certainly contributed to the development of electrical engineering science and education both in Kharkov and in Ukraine. He was one of the organizers and promoters of the radio engineering direction in Ukraine, participated in the work of public organizations and electrical congresses. His colleague at KhTI, Professor of chemistry Pavlo Dedusenko, is undoubtedly an outstanding person. As an active member of various charities, he worked hard for the public. These are both scientific societies and various social projects. A supporter of Ukrainian nationalism, he strove for the Independence of Ukraine, the development of Ukrainian culture. Repressed in 1945, the scientist died in the concentration camp in 1946. In 1991, due to the lack of evidence confirming the guilt of Pavlo Dedusenko, the professor was rehabilitated.

Мета дослідження – на основі опрацювання наукової літератури та архівних матеріалів провести комплексний історико-науковий аналіз життєвого шляху та науково-організаційної діяльності професорів Харківського технологічного інституту Олексія Хінкулова та Павла Дедусенка. На основі залучення невідомих та маловідомих архівних документів здійснено історичну реконструкцію творчої діяльності вчених, зокрема ретельно досліджено маловідомий період їхнього життя впродовж 1940-1946 рр. Проведено комплексний аналіз наукової діяльності Олексія Хінкулова, окреслено його внесок у становлення електротехнічної галузі. Підкреслено його роль у розгортанні в Україні наукових досліджень в галузі радіотехніки. Вчений очолював один з найбільших радіотехнічних гуртків України. Досліджено громадську діяльність Олексія Хінкулова, встановлено, що тривалий час він працював заступником голови, а далі головою Всеукраїнської асоціації інженерів, яка об'єднувала колективи науково-дослідних кафедр технічних закладів України. Наукова та організаційна діяльність професора Олексія Хінкулова безумовно сприяла розвитку електротехнічної науки й освіти як в Харкові так і в Україні. Він був одним з організаторів та популяризаторів радіотехнічного напряму в Україні, брав участь у роботі громадських організацій та електротехнічних з'їздів. Його колега по ХТІ професор хімії Павло Дедусенко безумовно непересічна особистість. Активний учасник різних благодійних товариств, він багато працював для громадськості. Це як наукові товариства так і різні проекти соціального спрямування. Прихильник українського націоналізму він прагнув незалежності України, розвитку української культури. Репресований повторно 1945 р. вчений помер у таборі у 1946 р. У 1991 р. з огляду на відсутність доказів, що підтверджували провину Павла Дедусенка, науковця було реабілітовано.
Професори Харківського технологічного інституту: невідомі сторінки біографії
Keywords: Oleksii Khinkulov; Pavlo Dedusenko; Kharkiv Technological Institute; higher technical education; Ukraine; Олексій Хінкулов; Павло Дедусенко; Харківський технологічний інститут; історія НТУ "ХПІ"; вища технічна освіта; Україна